2018
DOI: 10.1371/journal.pone.0197709
|View full text |Cite
|
Sign up to set email alerts
|

A methodological approach to identify agro-biodiversity hotspots for priority in situ conservation of plant genetic resources

Abstract: Agro-biodiversity is seriously threatened worldwide and strategies to preserve it are dramatically required. We propose here a methodological approach aimed to identify areas with a high level of agro-biodiversity in which to set or enhance in situ conservation of plant genetic resources. These areas are identified using three criteria: Presence of Landrace diversity, Presence of wild species and Agro-ecosystem ecological diversity. A Restrictive and an Additive prioritization strategy has been applied on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…Agricultural and environmental conditions obviously also contributed to this phenomenon. In the research found in [60], in fact, areas with a high level of agrobiodiversity in which to set or enhance in situ conservation of plant genetic resources (most appropriate areas (MAPAs)) were identified through a methodological approach using three criteria: pres- Apart from a few exceptions, the areas richest in number of landraces and in different crops cultivated as landraces were located inland in hilly and mountainous areas of the Apennine chain that are characterized by high environmental diversity. The Apennines is a land system that preserves, and in some case enhances, the biological diversity threatened by changes in land use and by diffuse abandonment [58,59].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Agricultural and environmental conditions obviously also contributed to this phenomenon. In the research found in [60], in fact, areas with a high level of agrobiodiversity in which to set or enhance in situ conservation of plant genetic resources (most appropriate areas (MAPAs)) were identified through a methodological approach using three criteria: pres- Apart from a few exceptions, the areas richest in number of landraces and in different crops cultivated as landraces were located inland in hilly and mountainous areas of the Apennine chain that are characterized by high environmental diversity. The Apennines is a land system that preserves, and in some case enhances, the biological diversity threatened by changes in land use and by diffuse abandonment [58,59].…”
Section: Resultsmentioning
confidence: 97%
“…Agricultural and environmental conditions obviously also contributed to this phenomenon. In the research found in [60], in fact, areas with a high level of agrobiodiversity in which to set or enhance in situ conservation of plant genetic resources (most appropriate areas (MAPAs)) were identified through a methodological approach using three criteria: presence of landrace diversity, presence of wild species, and agroecosystem ecological diversity. Considering their additive strategy (AS), it is not surprising that they match the hotspots identified.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their role in protecting wild ecosystems, natural parks can play a role in the conservation of crop genetic resources [26]. Natural parks tend to be isolated from intensive agricultural areas, and this separation can help protect fields where landraces are cultivated from the transmission of some pests and diseases as well as of genes in pollen from improved varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Hotspots of both biodiversity and agro-biodiversity have long relied on counting numbers of species (i.e., species richness; Figure 5 a) and assessing threats ( Figure 5 b). While biodiversity scientists have mainly focused on numbers of rare species (including many narrowly distributed taxa) for conservation, agronomists have been interested in diversity within gene pools (i.e., numbers of domesticated species and wild relatives) [ 27 , 28 , 85 ] and within crops (e.g., numbers of landraces) [ 112 ]. Although taxon counts remain extremely useful, new approaches are now proposed to account for the multi-faceted nature of (agro-)biodiversity, such as functional diversity accounting for the diversity in species chemical properties and eco-/agri-system functions [ 113 ], phylogenetic diversity as a potential proxy for functional and property diversity ( Figure 5 c) or for identifying gene sources for breeding programmes ( Figure 5 d).…”
Section: Towards a Unified Concept Of Agro-biodiversity Hotspotmentioning
confidence: 99%